Control of autoimmune arthritis by herbal extracts and their bioactive components - Shivaprasad H. Venkatesha; Brian Astry; Siddaraju M. Nanjundaiah; Hong R. Kim; Rajesh Rajaiah; Yinghua Yang; Li Tong; Hua Yu; Brian M. Berman; Kamal D. Moudgil (Elsevier, 2016)
Autoimmune diseases such as rheumatoid arthritis (RA) cause significant morbidity and loss of productivity. Many potent conventionally used drugs are available for these diseases, but their prolonged use is accompanied by severe adverse effects besides a high cost. Therefore, there is an unmet need for effective but less expensive medications for RA and other autoimmune diseases. Natural plant products belonging to the traditional systems of medicine, such as the traditional Chinese medicine and Indian Ayurvedic medicine, offer a vast and promising resource in this regard. However, herbal medicinal products are often poorly characterized for their composition as well as mechanisms of action. We review here the results of our systematically performed studies aimed at defining the anti-arthritic activity of three herbal extracts, namely, modified Huo-luo-xiao-ling dan (HLXL), Celastrus aculeatus Merr., and polyphenolic fraction of green tea (Camellia sinensis), as well as a purified compound Celastrol, a bioactive component of Celastrus. Specifically, we examined the effects of these herbal products on the immunological, biochemical and molecular biological effector pathways in autoimmune arthritis. We have also reviewed here related studies on these herbal products by other investigators. Taken together, we suggest further testing of these herbal products in RA patients.